1984
DOI: 10.1159/000179857
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Aminobutyric Acid Is not Likely a Physiological Prolactin-Inhibiting Factor

Abstract: Basal plasma prolactin concentration is controlled by tonic inhibition. The major prolactin-inhibiting factor (PIF) is believed to be dopamine. Factors other than dopamine have also been suggested as possible physiological PIF. One of the major candidates for the nondopaminergic PIF is considered to be gamma-aminobutyric acid (GABA). We have carefully examined the possible physiological role of GABA by monitoring, at every 2 min, the circulating prolactin concentration after GABA administration, in conscious f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The effects of ethanolamine-O-sulfate on the hypothalamic and anterior pituitary GABA concentration and prolactin secretion occur much earlier than the increase of GABA concentration in the peripheral plasma, indicating that circulating GABA does not play a functional role in the control of prolactin secretion (56). It should be mentioned, however, that the physiological importance of GABA in the hypophysial portal blood has been subsequently challenged by others (1247,1619). Nevertheless, the physiological role of GABA in regulating prolactin secretion is further supported by a close temporal relation between daily fluctuations in the activity of the tuberoinfundibular GABAergic system and the circadian prolactin surges (293).…”
Section: Amino Acidsmentioning
confidence: 99%
“…The effects of ethanolamine-O-sulfate on the hypothalamic and anterior pituitary GABA concentration and prolactin secretion occur much earlier than the increase of GABA concentration in the peripheral plasma, indicating that circulating GABA does not play a functional role in the control of prolactin secretion (56). It should be mentioned, however, that the physiological importance of GABA in the hypophysial portal blood has been subsequently challenged by others (1247,1619). Nevertheless, the physiological role of GABA in regulating prolactin secretion is further supported by a close temporal relation between daily fluctuations in the activity of the tuberoinfundibular GABAergic system and the circadian prolactin surges (293).…”
Section: Amino Acidsmentioning
confidence: 99%
“…However, close examination of the effects of GABA showed that it is not a physiological PIF . GABA and its agonists inhibit prolactin release in a dose-related manner in vitro (Enjalbert et al, 1979;Schally et al 1977;Shin et al, 1984), but a GABA agonist or antagonist does not inhibit or stimulate, respectively, prolactin release in conscious freely moving rats . GABA cannot be involved in this ether-induced prolactin release since GABA is ineffective on prolactin release in in vivo system.…”
Section: Prolactin Releasing Hormone (Prf)mentioning
confidence: 99%
“…GABA may directly inhibit the activity of the hypothalamic tuberoinfundibular dopaminergic pathway, with a resulting increase in prolactin secretion . It has also been reported that GABA exerts a dual control and can also have an inhibitory effect on prolactin release by acting at GABA receptors in the anterior pituitary gland, but this effect is less clear in vivo than in vitro. Only a few studies have evaluated the direct effects of GABAergic drugs on circulating basal prolactin levels in healthy subjects.…”
mentioning
confidence: 99%